BENTUK KOMUNIKASI FATIS DALAM BAHASA MANDAILING MASYARAKAT RAMBAH TENGAH BARAT - Muhromi Zaini Ref; Misra Nofrita (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the forms of phatic communication used in the Mandailing language by the people of Rambah Tengah Barat Village, Rokan Hulu Regency, Riau Province. Phatic is a form of communication that does not focus on conveying information, but rather on maintaining and strengthening social relationships between speakers. This study uses a qualitative descriptive method with data collection techniques through direct observation, interviews, and conversation recordings. The results show that there are 30 data items that can be categorized into three phatic forms, namely phatic particles (14 data), phatic words (14 data), and phatic phrases (7 data). This study is expected to contribute to the documentation of regional languages, enrich functional linguistic studies, and demonstrate the role of language in maintaining social cohesion in minority communitiesBased on the results of the research that has been Central Rambah Village has various forms, namely phatic particles, phatic words, and phatic phrases.carried out, it can be concluded that phatic communication in the Mandailing language used by the people of West